The relationship between acculturative stress and psychological outcomes in international students: a systematic review and meta-analysis - Soufi Amlashi, Rasa; Majzoobi, Mohammadreza; Forstmeier, Simon (Frontiers in Psychology, 2024)
The current systematic review aimed to examine the relationship between acculturative stress (AS) and psychological outcomes in international students to determine the role AS may play in predicting the mental health of international students. The studies included in the current systematic review and meta-analysis had considered AS and its impact on psychological outcomes among international students studying abroad. After checking the studies found in our primary search through the scientific databases in terms of our eligibility criteria, 29 studies were included, of which 26 were eligible for a meta-analysis (total N=7247). Meta-analysis indicated a moderate mean correlation of AS with psychological outcomes like depression, life satisfaction, quality of life, vocational outcome expectations, drinking behaviors, resilience, health promotion behavior, psychological adjustment, psychological distress, negative affect, and mental health symptoms (r=.39) and depression (r = .41), respectively. The review of studies revealed a robust relationship between AS and increased negative psychological outcomes such as depression, psychological distress, and general stress, as well as decreased positive psychological outcomes such as psychological adjustment, mental health, life satisfaction, and quality of life.